2021
DOI: 10.1111/adb.13051
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific role for prefrontal cortical protein interacting with C kinase 1 in cue‐induced cocaine seeking

Abstract: Disruption of prefrontal glutamate receptor interacting protein (GRIP), which anchors GluA2‐containing AMPA receptors (AMPARs) into the synaptic membrane, potentiates cue‐induced cocaine seeking in both males and females. Protein interacting with C kinase 1 (PICK1) plays an opposing role to that of GRIP, removing AMPARs from the synapse. Consistent with our hypothesis that disruption of PICK1 in the mPFC would lead to a decrease in addiction‐like behaviour, we found that conditional deletion of PICK1 in the mP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…In PICK KO mice, we showed that the acute locomotor response to a single injection of cocaine was markedly attenuated. Moreover, in support of the role of PICK1 in neuroadaptive changes induced by cocaine, we observed a diminished self-administration of cocaine in the KO mice [82], and the conditional deletion of PICK1 in the medial prefrontal cortex attenuated cue-induced cocaine seeking in male mice [83]. In accordance with the results, i.v.…”
Section: Side-effects Associated With Current Pain Drugs Are Unlikely...supporting
confidence: 88%
See 1 more Smart Citation
“…In PICK KO mice, we showed that the acute locomotor response to a single injection of cocaine was markedly attenuated. Moreover, in support of the role of PICK1 in neuroadaptive changes induced by cocaine, we observed a diminished self-administration of cocaine in the KO mice [82], and the conditional deletion of PICK1 in the medial prefrontal cortex attenuated cue-induced cocaine seeking in male mice [83]. In accordance with the results, i.v.…”
Section: Side-effects Associated With Current Pain Drugs Are Unlikely...supporting
confidence: 88%
“…administration of tPD5 was shown to reduce the reinstatement of cocaine seeking in rats [80]. This suggest that PICK1 does not constitute a neutral target with respect to reinforcing behavior, but its inhibition might actually counteract the reinforcing effects of, for example, opioids, although the gender aspects in relation to abuse liability need a more thorough investigation [83]. Consequently, pharmacological interference with the PICK1 function could serve as an effective substitution/transition treatment option for opioids, for example, in late stages of post-surgical pain relief, and for chronic pain patients suffering from opioid addiction.…”
Section: Side-effects Associated With Current Pain Drugs Are Unlikely...mentioning
confidence: 99%
“…PICK1 protein levels were more abruptly reduced in female HET and KO DAT rats that in males, when compared to their same sex WT controls. Recently, Wickens et al [ 82 ], highlighted relevant sex differences regarding alterations of PICK levels and their implication on the response to cocaine seeking (addictive) behavior. In line with our current results showing sex differences in PICK1–cocaine mediation, disruption of PICK (conditional deletion) increased cocaine seeking only in females, while it had opposite effects in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers will argue that investigating both males and females is only important in the first step and thus the use of both sexes in further experiments, beyond the initial study is not required. However, there are plenty of examples where a trait may not have sex differences but the mechanisms underlying that trait do show significant differences between males and females (Oberlander and Woolley, 2016; Sorge et al, 2015; Wickens et al, 2021; Yagi et al, 2020). Thus, it is important for researchers to understand that using males and females in one experiment does not preclude the fact that they may show differences in further experiments, as others have discovered.…”
Section: Discussionmentioning
confidence: 99%